Social inequalities in early childhood competences, and the relative role of social and emotional versus cognitive skills in predicting adult outcomes. (4th May 2021) - Schoon, Ingrid; Nasim, Bilal; Cook, Rose
Abstract : This study draws on the nationally representative British Birth Cohort Study (BCS70) to examine (1) the association between social background and early socio‐emotional and cognitive competences at age 5 and (2) the relative and independent contributions of early socio‐emotional and cognitive competences to educational and socio‐economic attainment in adulthood. A multi‐dimensional (multiple exposure, multiple outcome) approach is adopted in conceptualising social background, childhood competences and adult outcomes by age 42. Indicators of social background include parental education, social class, employment status, family income, as well as home ownership, enabling us to test which aspects of socio‐economic risk uniquely influence the development of early competences. Indicators of childhood competences include directly assessed cognitive competences (i.e. verbal and visual motor skills), while measures of socio‐emotional competences include hyperactivity, good conduct, emotional health and social skills, reported by the child's mother at age 5. Adult outcomes include highest qualifications, social class and household income by age 42. The findings suggest that multiple indicators of social background are associated with both socio‐emotional and cognitive competences, although the associations with socio‐emotional competences are less strong than those with cognitive competences. We find significant long‐term predictive effects of early cognitive skills on adult outcomes, but also independent effects of socio‐emotional competences, in particular self‐regulation, over and above the role of family background. The study supports calls for early interventions aiming to reduce family socio‐economic risk exposure and supporting the development of cognitive skills and self‐regulation (i.e. reducing hyperactivity and conduct problems).